Minimally Invasive Approaches for Combined Gynecologic Surgeries: Our Three Years Clinical Experiences - İlknur İnegöl Gümüş; Önder Sürgit; Aysel Uysal; Serap Simavlı; Ayla Eser; İkbal Kaygusuz (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: To evaluate outcomes of gynecological patients with multiple pathologic conditions who were treated with combined laparoscopic procedures.